Analysis of Rice Field Farming Income in Ogogasang Village, Dondo District, Tolitoli Regency: Pengaruh Produksi Gula Aren terhadap Pendapatan Masyarakat di Desa Dadakitan Kecamatan Baolan Kabupaten Tolitoli - Winarsih Nasir, Yuyun (STIE MUJAHIDIN TOLITOLI, 2025)
This study aims to determine the Influence of Palm Sugar Production on Community Income in Dadakitan Village, Baolan District, Tolitoli Regency. This study uses an associative quantitative research method to determine the influence of independent variables on dependent variables, data sources obtained from observations, interviews, documentation and questionnaires and the type of data is primary data and secondary data with a total of 85 respondents in Dadakitan Village, Baolan District, Tolitoli Regency. Based on the research that has been carried out by collecting data from the results of the research questionnaire with the help of the SPSS Version 26 data processing application, it can be concluded that the results of the hypothesis test have a partial influence between production and income. This is proven by the results of the t-test which shows a Sig. value of 0.000 < 0.05 and a calculated t-value of 11.085 > a table t-value of 1.992. with the variable influence of palm sugar production level on community income of 59.7%. In addition, palm sugar production also helps the economy of the community in Dadakitan village, especially for palm sugar artisans from their production are able to meet their daily needs.